Altered liver sinusoidal endothelial cells in MASLD and their evolution following lanifibranor treatment - Pierre-Emmanuel Rautou; Shivani Chotkoe; Louise Biquard; Guillaume Wettstein; Denise van der Graaff; Yao Liu; Joris De Man; Christophe Casteleyn; Sofie Thys; Winnok H. De Vos; Pierre Bedossa; Michael P. Cooreman; et al. (JHEP Reports)
Background & Aims: Data on changes in liver sinusoidal endothelial cells (LSECs) in patients with metabolic dysfunction-associated steatotic liver disease (MASLD) and their response to treatment are limited. This study aimed at determining (i) features associated with LSEC capillarisation in patients with MASLD; (ii) whether LSEC changes can regress with the pan-peroxisome proliferator-activated receptor (PPAR) agonist lanifibranor; (iii) the role of the different PPAR isotypes on LSEC changes in MASLD. Methods: We analysed CD34 expression, a marker of LSEC capillarisation, on liver biopsies from patients considered for inclusion in the NATIVE trial at baseline (n = 249), and after 24 weeks of placebo or lanifibranor (n = 173). Two rat models of MASLD were used to investigate the effect of lanifibranor or of mono-PPAR agonists on LSECs. Results: Lobular CD34 staining was more intense in patients with isolated steatosis than in those with no MASLD (52% vs. 10%; p = 0.03). In the overall cohort, this staining was more intense in patients with metabolic dysfunction-associated steatohepatitis (MASH) than in those without (63% vs. 41%; p = 0.01) and strongly correlated with liver fibrosis and to a lesser extent with liver inflammation. Lanifibranor treatment was associated with more common improvement in CD34 periportal staining (p = 0.025), and less frequent worsening of lobular staining (p = 0.028). Compared with healthy rats, rats with MASLD had higher CD34 staining, portal venous pressure, intrahepatic vascular resistance, and impaired liver endothelial function. Lanifibranor normalised or strongly improved these abnormalities, whereas mono-PPAR agonists caused partial improvements. Conclusions: In patients, LSEC capillarisation was increased at the earliest stages of MASLD and was associated with liver fibrosis and inflammation. In both patients and rats with MASLD, lanifibranor treatment was associated with improvement in liver endothelial phenotype. Impact and implications: Data on changes in liver sinusoidal endothelial cells (LSECs) in patients with metabolic dysfunction-associated steatotic liver disease (MASLD) and their response to treatment are limited. This study demonstrates that LSEC capillarisation is already present in the lobular zone of the liver of patients and rats at the stage of isolated steatosis, before metabolic dysfunction-associated steatohepatitis (MASH) onset, and progresses with liver fibrosis, and to a lesser extent with liver inflammation. Lanifibranor treatment, a pan-peroxisome proliferator-activated receptor agonist currently tested in a phase III clinical trial, improves LSEC capillarisation but also intrahepatic vascular resistance and portal pressure in MASLD. Targeting LSECs appears to be a promising approach to improve MASH.